Analysis of Internet Review Site Comments for Spine Surgeons: How Office Staff, Physician Likeability, and Patient Outcome Are Associated With Online Evaluations - Donnally, 3rd, Chester J; Roth, Eric S; Li, Deborah J; Maguire, Jr, James A; McCormick, Johnathon R; Barker, Grant P; Rivera, Sebastian; Lebwohl, Nathan H (Spine (Philadelphia, Pa. 1976), 2018)
Observational study. To evaluate how online patient comments will affect website ratings for spine surgeons. With the ever-growing utilization of physician review websites, healthcare consumers are assuming more control over whom they choose for care. We evaluated patient feedback and satisfaction scores of spine surgeons using comments from three leading physician rating websites: Healthgrades.com, Vitals.com, Google.com. This is the largest review of online comments and the largest review of spine surgeon comments. From the North American Spine Society (NASS) membership directory, 210 spine surgeons practicing in Florida (133 orthopedic trained; 77 neurosurgery trained) with online comments available for review were identified, yielding 4701 patient comments. These were categorized according to subject: (1) surgeon competence, (2) surgeon likeability/character, (3) office staff, ease of scheduling, office environment. Type 1 and 2 comments were surgeon-dependent factors whereas type 3 comments were surgeon-independent factors. Patient comments also reported a score (1-5), 5 being the most favorable and 1 being the least favorable. There were 1214 (25.8%) comments from Healthgrades, 2839 (60.4%) from Vitals, and 648 (13.8%) from Google. 89.9% (4225) of comments pertained to surgeon outcomes and likeability (comment type 1 and 2), compared with 10.1% (476) surgeon-independent comments (comment type 3) (P < 0.0001). There was a significantly higher number of favorable ratings associated with surgeon-dependent comments (types 1 and 2) compared with surgeon-independent comments (type 3). Surgeon-independent comments were associated with significantly lower scores compared with comments regarding surgeon-dependent factors on all review sites. Spine surgeons are more likely to receive favorable reviews for factors pertaining to outcomes, likeability/character, and negative reviews based on ancillary staff interactions, billing, and office environment. Surgeons should continue to take an active role in modifying factors patients perceive as negative, even if not directly related to the physician. 3.